2016
DOI: 10.3329/agric.v13i2.26587
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weather on Sigatoka Leaf Spot of Banana (<i>Musa</i> spp. L.) and its Ecofriendly Management

Abstract: A study was carried out during July 2010 to April 2012 to understand the effect of weather prevalence on sigatoka disease of banana suckers in different areas of Bangladesh and to develop an environment friendly disease management practice. Four locations viz. Dinajpur, Bogra, Rangpur and Madhupur were surveyed. To find out suitable and ecofriendly management practices for controlling sigatoka disease of banana, seven treatments were used viz. i) Soil drenching with BAU-Biofungicide (2%), ii) BAU-Biofungicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
8
1
3
Order By: Relevance
“…Rainfall appeared to have little or no impact on disease severity, contradictory to studies that reported that leaf wetness was critical for P. fijiensis spore germination, symptom development and disease severity [49,50]. Our observations suggest that conidia, whose germination is not affected by leaf wetness [50], is the main source of inoculum and played an important role in the spread and severity of black Sigatoka in this study.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Rainfall appeared to have little or no impact on disease severity, contradictory to studies that reported that leaf wetness was critical for P. fijiensis spore germination, symptom development and disease severity [49,50]. Our observations suggest that conidia, whose germination is not affected by leaf wetness [50], is the main source of inoculum and played an important role in the spread and severity of black Sigatoka in this study.…”
Section: Discussioncontrasting
confidence: 96%
“…High RH is important in conidia formation. Conidia serves to initiate multiple reinfections during the growing season, increasing the number and size of lesions while maximum temperature influences the lesion formation, expansion and rate of leaf necrosis [50]. Rainfall appeared to have little or no impact on disease severity, contradictory to studies that reported that leaf wetness was critical for P. fijiensis spore germination, symptom development and disease severity [49,50].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the coastal region of Ecuador there are small variations in temperature and luminosity from one season to the rest, but precipitations are concentrated in the winter period (usually from January to May). The rain and humidity of the winter season favor the spread of Sigatoka Negra across the banana trees (Jesus Júnior et al, 2008;Khan et al, 2015) and for this reason producers intensify fumigations in this period. 8 Figure 1 shows aerial fumigations in the provinces where most of the banana plantations in the country are concentrated.…”
Section: Plantations and Aerial Fumigationmentioning
confidence: 99%
“…Bananas (Musa spp. L.) are monocotyledonous plants that belong to the family Musaceae and it is one of the most important fruits in the world and is widely grown in the tropical and sub-tropical countries the genus Musa originated in Southeast Asia (Khan et. al, 2015).…”
Section: Introductionmentioning
confidence: 99%